Ovarian cancer at young age: the contribution of mismatch-repair defects in a population-based series of epithelial ovarian cancer before age 40. Issue 4 (1st July 2007) - Domanska, K.; Malander, S.; MÅSbÄCk, A.; Nilbert, M.
Abstract : At least one of ten patients with ovarian cancer is estimated to develop their tumor because of heredity with the breast and ovarian cancer syndrome due to mutations in the BRCA1 and BRCA2 genes and hereditary nonpolyposis colorectal cancer (HNPCC) being the major genetic causes. Cancer at young age is a hallmark of heredity, and ovarian cancers associated with HNPCC have been demonstrated to develop at a particularly early age. We used the Swedish Cancer Registry to identify a population-based series of 98 invasive epithelial ovarian cancers that developed before 40 years. Mucinous and endometrioid cancers were overrepresented and were diagnosed in 27% and 16% of the tumors, respectively. Immunostaining using antibodies against MLH1, PMS2, MSH2, and MSH6 was used to assess the mismatch-repair status and revealed loss of expression of MLH1/PMS2 in two cases, loss of MSH2/MSH6 in one case, and loss of MSH6 only in three tumors. A microsatellite instability–high phenotype was verified in five of six tumors. Based on the identified mutations and family history of cancer, several of these individuals are likely to be affected by HNPCC. We conclude that although the causes of the vast majority of epithelial ovarian cancer at young age are unknown, HNPCC should be considered because of the high risk of metachronous colorectal cancer in the individual and the possibility of preventing additional cancers in the family through control programs.